2021
DOI: 10.3390/s21051690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (100) and (001) Hexagonal WO3 Faceting on Isoprene and Acetone Gas Selectivity

Abstract: The hexagonal WO3 polymorph, h-WO3, has attracted attention due to its interatomic channels, allowing for a greater degree of intercalation compared to other WO3 polymorphs. Our research group has previously demonstrated h-WO3 to be a highly sensitive gas sensing material for a flu biomarker, isoprene. In this work, the gas sensing performance of this polymorph has been further investigated in two distinct configurations of the material produced by different processing routes. The first sample was synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Esophageal cancer, esophagogastric cancer, gastric cancer, pancreatic cancer Ag NWs modified with ZnO NPs [17] Isoprene Esophagogastric cancer, gastric cancer Hexagonal WO 3 [18] Isopropanol Lung cancer, COVID-19 MIL-100 (Fe) [19]…”
Section: Acetonementioning
confidence: 99%
“…Esophageal cancer, esophagogastric cancer, gastric cancer, pancreatic cancer Ag NWs modified with ZnO NPs [17] Isoprene Esophagogastric cancer, gastric cancer Hexagonal WO 3 [18] Isopropanol Lung cancer, COVID-19 MIL-100 (Fe) [19]…”
Section: Acetonementioning
confidence: 99%
“…Further, a metastable hexagonal polymorph (h-WO 3 , P6/mmm) that exhibits a large network of open hexagonal channels along the c-axis has been reported . It has been shown that this characteristic of h-WO 3 opens a wide range of applications in electrochemical, as well as in electrochromic appliances [6,7], as gas sensors [7][8][9][10] and in photo-catalysis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it seems impossible to obtain pure h-WO 3 from hydrothermal synthesis. Solvothermal synthesis using WCl 6 as precursor can obtain h-WO 3 free from alkaline ions [8,30,31]. Choi et al [30] has shown that h-WO 3 can be directly synthesized by solvothermal synthesis with WCl 6 as precursor and a water/ethanol mixture solution as solvent with a water content between 2 vol% and 10 vol%.…”
Section: Introductionmentioning
confidence: 99%
“…For a brief overview of the current research status of isoprene sensing SMOs, Table 1 summarises the materials studied and their sensing performances published during recent years (2020-2023). [13][14][15][16][17][18][19][20][21][22][23][24][25] The most investigated SMOs for VOC sensing were transition-metal oxides, including In 2 O 3 , SnO 2 , WO 3 , MoO 3 , TiO 2 , ZnO, and Co 3 O 4 , 26 which were usually doped with a small amount of another element (or elements) for higher sensitivity to a particular gas (i.e., the selectivity for this gas). Several of the above SMOs, i.e., In 2 O 3 , 20 ZnO, 17 WO 3 , 21 and Co 3 O 4 , 25 have been studied for isoprene sensing and a number of elements, including Au, 17,21 Pt, 16 Pd, 20 Ti, 27 and Si, 12 have been tried as dopants.…”
Section: Introductionmentioning
confidence: 99%
“…For a brief overview of the current research status of isoprene sensing SMOs, Table 1 summarises the materials studied and their sensing performances published during recent years (2020–2023). 13–25…”
Section: Introductionmentioning
confidence: 99%